PERFORMANCE ANALYSIS WITH BALANCED SCORECARD APPROACH IN TIRTA HANDAYANI MUNICIPAL WATERWORKS (PDAM) GUNUNGKIDUL DISTRICT - Puspitaliza, Afifah; Novitasari, Budi Tiara (Balance: Jurnal Riset Akuntansi dan Bisnis, 2023)
This research aims to investigate performance achievements achieved at PDAM Tirta Handayani in Gunungkidul Regency, Yogyakarta Special Region, in 2020 and 2021 using the Balanced Scorecard approach. This study consists of the independently audited financial statements in 2020 and 2021. This research is quantitative descriptive. The method used is the Balanced Scorecard, which performs calculations on four perspectives such as financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. Also one additional new perspective, namely sustainability. The results of the study show that the performance achievements in 2020 received a score of 3.30 in the "high performance" predicate, while in 2021 they also received a score of 3.37 in the "high performance" predicate. Performance achievements from 2020 to 2021 have increased by 0.07 due to an increase in the financial perspective, internal business processes, although there has been a decrease in the customer perspective.